BPJS PATIENT BILLING CLAIMS: STUDY ON HOSPITAL POLYCLINIC SERVICES AS OUTPATIENT REVENUE - Ritonga, Sepriana; Azmi, Zul (Politeknik Negeri Bengkalis, 2023)
Several issues have been raised regarding the uneven payment of bills related to BPJS health insurance. The purpose of this study is to contribute to the accountability of BPJS patient billing claims for outpatient services at the Hospital as outpatient income. The flow of BPJS special patient services from reception to settlement of claims is the focus for identifying pending services. Design/Methodology/Approach: this qualitative research uses in-depth interviews with relevant informants. Interviews were conducted with the head manager of the KMKB, the head of the BPJS officer's office and two outpatient coder staff. We also conducted a triangulation test to test the validity of the data. The data from the interviews were then analyzed to explain the findings. Findings: several technical findings are the cause of claims for bad claims, including claims of outpatients and inpatients on the same day and date, incomplete medical resumes filled out by the doctor in charge of the patient, patients who are referred back but the time period has expired, network problems when accessing INA CBG's, and delays in settlement of claims so that the BPJS claim period expires. Originality/Values: This research offers unique insight into health services related to BPJS patient claims services by explaining how to understand them and anticipate pending claims or claims that cannot be disbursed through the results of qualitative research using an in-depth interview approach.